Fatores erosivos e a sua influência na morfologia de voçorocas no município de Cacequi, Rio Grande do Sul - Rademann, Lucas Krein (2024)
Gully erosion is the form of erosion with the greatest environmental and economic impact, causing loss of fertile soil, silting up of rivers, and changes in the landscape and drainage channels. These are complex processes, involving several erosive mechanisms that vary in type and intensity over the time of evolution of the erosion feature. This complexity leads to the development of the most variable forms of gullies, as in the case of the upstream river basin of the Areal do Limeira River in Cacequi - RS, where the gullies show different shapes and intensities in a small space, despite the small variation in erosive factors, making it necessary to analyze in detail the factors that determine this differentiation. This thesis hypothesizes that in the Pirambóia Formation, local lithopedological and relief changes influence the shape and erosion mechanisms of the gullies. Thus, the general aim of this work is to evaluate the influence of geomorphological factors and land use on the morphology and development of three gullies in the headwaters of the Areal do Limeira River basin. To this end, UAV flights were carried out over the three gullies to obtain high spatial resolution DTMs and orthomosaics to perform the morphometry of the gullies and classify them. The spatial variation of soil and rock characteristics in the study area, the main aspects of the relief of the catchment areas, and the land use were also mapped and analyzed. V1 gully is the largest of the three studied, presenting variation in depth and erosive mechanisms acting on it. V2 is the shortest, widest and deepest, presenting mass movements throughout almost its entire extension. V3 presented the longest, shallowest, and less eroded volume, in response to less intense mass movements and more stable side walls. Although several factors that influence erosion mechanisms and the shape of gullies, the type of soil material proved to be a determining factor in the erosion mechanisms involved. Sandy materials proved to be more prone to mass movements, vertical development and the concentration of joints and fractures, while predominantly clayey materials proved to be more cohesive and resistant to erosion, especially subsurface erosion, resulting in fewer occurrences of mass movements. The results presented in this work help to understand the accelerated erosion processes in the pampa biome area in western Rio Grande do Sul, elucidating the main factors that influence the shape and expansion of gullies, which is extremely important for determining effective conservation practices.